Non‐pharmacological strategies to reduce stress and anxiety in endovascular procedures: A scoping review - Francisco de Cassio de Oliveira Mendes; Kauanny Vitoria Gurgel dos Santos; Joyce Karolayne dos Santos Dantas; Sara Cristina Matias de Araújo; Fernanda de Castro Teixeira; Karena Cristina da Silva Leal; Daniele Vieira Dantas; Rodrigo Assis Neves Dantas (Wiley, 2024)
Abstract Aim This study aimed to identify and map the production of knowledge on non‐pharmacological strategies to reduce stress and anxiety in patients undergoing endovascular procedures. Design Scoping review. Methods The review was performed using the PRISMA‐ScR guidelines. The searches were conducted in Scopus, PubMed, Web of Science, Wiley Online Library, BVS/BIREME, Lilacs, Gale Academic OneFile, SciELO, Cochrane Library, CAPES Catalog of Dissertations and Theses, Oswaldo Cruz Foundation Portal of Theses and Dissertations, and Theses and Dissertations from Latin America. Results Twenty‐two articles were selected. The articles were published from 2001 to 2022, mostly in Iran, and there was a predominance of randomized clinical trials. The Spielberger State‐Trait Anxiety Inventory was the most used instrument. The findings indicated that music therapy, educational guidelines or videos on the procedure, massage, psychological preparation and aromatherapy were the main non‐pharmacological therapies used to reduce anxiety and stress in patients undergoing vascular procedures.